On the trail of John Calvin's philosophy of language: a few notes on his commentary on Genesis 10 and 11 - N. T. van der Merwe (Acta Theologica)
This essay attempts to discover John Calvin’s view on the nature and use of human language. It suggests a strategy for establishing a few building blocks of his philosophy of language. For this purpose Calvin’s Commentary on Genesis is analysed and commented on. Seven items to be incorporated in the structure are found to be important but inadequate. As a follow-up the author refers  to the contemporary paradigm shift of linking the philosophy of language to contextual studies, pragmatics, rhetoric, ethics and hermeneutics.